Penanaman Religiusitas Keislaman Berorientasi pada Pendidikan Multikultural di Sekolah - A. Suradi (UIN Sunan Ampel Surabaya, 2018)
This article describes how multicultural education responds to demographic changes and religious culture in school environment, and even society as a whole. Thus, it aims to foster attitudes and values which are essential to social life and peace buiding among religious followers. This article is a library research using qualitative descriptive approach. There are two approaches to propose in creating Islamic education with multiculturalism foundation, conceptually and methodologically. The conceptually means to enrich selves with multiculturalism issues from various resources. Next, the methodologically means to promote educating fugure (such as teachers) to act practically in spreading multiculturalism. Therefore, the values of Islamic education with multicultural foundation would significantly support the creation of religious understanding among students through both curriculum contents and learning process.